Cretaceous long-distance lithospheric extension and surface response in South China - Li, Jianhua; Dong, Shuwen; Cawood, Peter A.; Thybo, Hans; Clift, Peter D.; Johnston, Stephen T.; Zhao, Guochun; Zhang, Yueqiao (Earth-science reviews, 2023)
Lithospheric extension plays a pivotal role in governing the evolution of continents and the birth of oceanic basins on Earth. Despite this, quantifying wide-mode lithospheric extension and its effects on surface uplift remain elusive. The vast (> 800-km-wide) Cretaceous extensional system in South China offers a unique opportunity to study the processes and mechanism(s) of wide-mode extension and their impacts. Here we review the essential constraints from crustal and mantle structures determined from geological, seismic reflection/refraction, and other geophysical data. Our compilation reveals a stratified lithosphere with depth-dependent extension in a magma-poor domain, expressed by normal faulting in the upper crust, ductile stretching in the mid-lower crust, and localized Moho uplift associated with mantle shear zones. From the magma-poor domain to the magma-rich domain, lateral variations in the extensional mode involve increased crustal melting, decreased crust-mantle decoupling, and mantle shear-zone abandonment caused by magmatic underplating. Extension-related strain fields across the South China lithosphere are uniformly NW-SE oriented, indicating vertically coherent deformation. Stress transmission across this coherent system likely occurred via basal traction and localized mantle shearing. Lower-crustal stretching and lithospheric removal accompanied and promoted the tectonic exhumation of extensional domes and mountain ranges. We propose a coupling between slab rollback, mantle flow, and lithospheric extension. Rollback-induced mantle flow likely drove lithospheric extension in South China by imposing shear forces at the lithosphere base. •We review the deep processes of Cretaceous long-distance extension in South China.•Our data compilation reveals a stratified lithosphere with depth-dependent extension.•We clarified lateral variations in extension modes across the >800-km-wide system.•We propose a coupling between slab rollback, mantle flow, and lithospheric extension.